Best practice for providing social care and support to people living with concurrent sight loss and dementia: professional perspectives. Issue 2 (13th June 2016) - Evans, Simon Chester; Bray, Jennifer
Abstract : Purpose: – Approximately 100, 000 people in the UK aged 75 and over have concurrent dementia and sight loss, but current understanding of their experiences, needs and preferences is limited. The purpose of this paper is to report on a research project that explored the provision of social care and support for older people with both conditions. Design/methodology/approach: – The project was a collaboration between the universities of York, Worcester, Bournemouth and Cambridge, supported by the Thomas Pocklington Trust and the Housing and Dementia Research Consortium. Data for this paper were drawn from focus groups held in 2013 involving 47 professionals across the dementia, sight loss and housing sectors. Findings: – Thematic analysis identified five main barriers to providing high-quality, cost-effective social care and support: time constraints; financial limitations; insufficient professional knowledge; a lack of joint working; and inconsistency of services. The requirements of dementia and sight loss often conflict, which can limit the usefulness of equipment, aids and adaptations. Support and information needs to address individual needs and preferences. Research limitations/implications: – Unless professionals consider dementia and sight loss together, they are unlikely to think about the impact of both conditions and the potential of their own services to provide effective support for individuals and their informal carers. Failing to consider both conditions together can also limit the availability and accessibility of social care and support services. This paper is based on input from a small sample of self-selecting professionals across three geographical regions of England. More research is needed in this area. Practical implications: – There are growing numbers of people living with concurrent dementia and sight loss, many of whom wish to remain living in their own homes. There is limited awareness of the experiences and needs of this group and limited provision of appropriate services aids/adaptations. A range of measures should be implemented in order to support independence and well-being for people living with both conditions and their family carers. These include increased awareness, improved assessment, more training and greater joint working. Social implications: – People living with dementia or sight loss are at high risk of social isolation, increasingly so for those with both conditions. Services that take an inclusive approach to both conditions can provide crucial opportunities for social interaction. Extra care housing has the potential to provide a supportive, community-based environment that can help residents to maintain social contact. Originality/value: – This paper adds much-needed evidence to the limited existing literature, and reflects the views of diverse professionals across housing, health and social care.